Radio system design for telecommunications - Roger L. Freeman (Wiley, 2006)
The Third Edition of Radio System Design for Telecommunications brings this highly acclaimed book fully up to date with the latest technological advances and new applications. At the same time, the hallmarks of the previous editions, including the text's popular tutorial presentation, have been retained. Readers therefore get all the tools and guidance they need to master an essential set of current design techniques for radio systems that operate at frequencies of 3 MHz to 100 GHz